Fluorescence in situ hybridization with human chromosome-specific libraries: detection of trisomy 21 and translocations of chromosome 4. - Pinkel, D (1988)
Chromosomes can be specifically stained in metaphase spreads and interphase nuclei by in situ hybridization with entire chromosome-specific DNA libraries. Unlabeled human genomic DNA is used to inhibit the hybridization of sequences in the library that bind to multiple chromosomes. The target chromosome can be made at least 20 times brighter per unit length than the others. Trisomy 21 and translocations involving chromosome 4 can be detected in metaphase spreads and interphase nuclei by using this technique.